14N Nuclear quadrupole coupling and methyl internal rotation in the microwave spectrum of 2-methylpyrrole. (2nd June 2020) - Nguyen, Thuy; Dindic, Christina; Stahl, Wolfgang; Nguyen, Ha Vinh Lam; Kleiner, Isabelle
Abstract : Using two molecular jet Fourier transform microwave spectrometers, the rotational spectrum of 2-methylpyrrole was recorded in the frequency range from 2 to 40 GHz. From the torsional splittings due to the internal rotation of the methyl group a barrier height of 279.7183(26) cm −1 was deduced. Because of the 14 N nucleus, all lines show a quadrupole hyperfine structure. The microwave spectra were analysed using the XIAM and BELGI-Cs -hyperfine codes. The XIAM code enabled us to reproduce the whole data set with a root-mean-square deviation of 5.6 kHz while the BELGI-Cs -hyperfine code could provide a better root-mean-square almost by a factor of 2 compared to that of XIAM . The experimental results were complemented by quantum chemical calculations. The values of the methyl torsional barrier and the 14 N nuclear quadrupole coupling constants are discussed and compared with other methyl substituted pyrroles as well as other aromatic five-membered rings. GRAPHICAL ABSTRACT: